Effects of time-restricted feeding (TRF)-model of intermittent fasting on adipose organ: a narrative review - Zahra Bahadoran; Parvin Mirmiran; Khosrow Kashfi; Asghar Ghasemi (Eating and Weight Disorders)
Abstract Time-restricted feeding (TRF), an intermittent fasting approach involving a shortened eating window within 24 h, has gained popularity as a weight management approach. This review addresses how TRF may favor fat redistribution and the function of the adipose organ. TRF trials (mainly 16:8 model, with a duration of 5–48 weeks) reported a significant weight loss (1.2–10.2%, ~ 1.4–9.4 kg), with a considerable decrease in total fat mass (1.6–21%, ~ 0.5–7 kg) and visceral adipose compartment (VAC, 11–27%) in overweight and obese subjects. Experimental TRF in normal-fed and obesogenic-diet-fed mice and rats (with a fasting duration ranging between 9 and 21 h within 1–17 weeks) reported a significant reduction in body weight (~ 7–40%), total fat mass (~ 17–71%), and intrahepatic fat (~ 25–72%). TRF also improves VAC and subcutaneous adipose compartment (SAC) function by decreasing adipocyte size, macrophage infiltration, M1-macrophage polarity, and downregulating inflammatory genes. In conclusion, beyond its effect on body weight loss, total fat mass, and intrahepatic fat accumulation, TRF favors adipose organ fat redistribution in overweight and obese subjects by decreasing VAC and improving the function of VAC and SAC.